Antecedente de anemia ferropénica asociado a caries dental en niños de 3 a 5 años del Centro Poblado los Delfines Iquitos 2024 - Gómez Cárdenas, Zaida Gabriela (2025)
The objective of this study was to determine the association between anemia level and dental caries index in children aged 3 to 5 years at the Los Delfines Population Center in Iquitos, 2024. The design was non-experimental, descriptive, correlational, and cross-sectional. It used a quantitative approach, using documentary review techniques and home visits. The instruments used were the data collection form to identify children with anemia and the clinical odontogram record (CEO-D Index). The sample consisted of 37 children who met the established criteria. Of the 283 children aged 3 to 5 years treated at the Los Delfines PSI-2, 37 children with anemia were identified: 54% were male and 46% were female; 56.8% had mild anemia; 35.1% had moderate anemia; and 8.1% had severe anemia. Regarding caries index, 32.4% had very low caries; among 3-year-old children, 33% had a low caries index, 28.6% of 4-year-olds, and 45.5% of 5-year-olds had a moderate caries index. It is concluded that an association was found between the level of anemia and the dental caries index in children aged 3 to 5 years treated at P.S. I-2 of the Los Delfines Population Center. The association level was estimated at 0.834, significant (p < 0.01). The proposed hypothesis was accepted.